STUDI KUALITAS AIR HASIL SARINGAN BAHAN KARBON AKTIF, PASIR SILIKA DAN KERIKIL - Almukarrama, Almukarrama; Iswadi, Iswadi; Said L, Muh (JFT : Jurnal Fisika dan Terapannya, 2015)
This research aims to find out theÂ  quality of the water as it had been filtered from the single of active carbon, silica sand and gravel as the media filter. And also to know the quality of the water as it had been filtered from the combination of active carbon, silica sand and gravel as the media filter. The quality of the water filtered was measured by both physic and chemistry parameters, either parameters were measured and observed directly at the Modern Physic Laboratory of Science and Technology Faculty and at the Physic Chemistry Laboratory of Â Science and Technology Faculty. The quality of the water which had been filtered by the aforementioned filter materials then met the requirement as pure water based on the water authentic quality standard (South Sulawesi Governor Rule Number 69, 2010), the water then can be used for the daily household necessity such as bathing, watering plant, laundry, and so forth.